1994
DOI: 10.1037/0022-3514.67.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in causal uncertainty.

Abstract: This article presents a scale that measures chronic individual differences in people's uncertainty about their ability to understand and detect cause-and-effect relationships in the social world: the Causal Uncertainty Scale (CUS). The results of Study 1 indicated that the scale has good internal and adequate test-retest reliability. Additionally, the results of a factor analysis suggested that the scale appears to be tapping a single construct. Study 2 examined the convergent and discriminant validity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 39 publications
9
158
1
1
Order By: Relevance
“…Indeed, different areas of research have demonstrated the effects of uncertainty for a variety of important goals. For instance, goals for prediction and control are served by attribution processes (Heider, 1958), and the effects of uncertainty in relationship to these goals are the focus of work on Causal Uncertainty (CU; Weary & Edwards, 1994). In addition to prediction and control, other important goals threatened by uncertainty include group identification (the focus of Uncertainty Identity Theory; Hogg, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, different areas of research have demonstrated the effects of uncertainty for a variety of important goals. For instance, goals for prediction and control are served by attribution processes (Heider, 1958), and the effects of uncertainty in relationship to these goals are the focus of work on Causal Uncertainty (CU; Weary & Edwards, 1994). In addition to prediction and control, other important goals threatened by uncertainty include group identification (the focus of Uncertainty Identity Theory; Hogg, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One common theoretical perspective on uncertainty is that it poses a potent self-threat. From Heider (1958) to Weary and Edwards (1994) and Hogg (2007), certain types of uncertainty are portrayed theoretically as aversive, and as a threat to prediction and control needs. This self-threat conceptualization of uncertainty suggests that self-enhancing manipulations might reduce some of uncertainty's effects, an idea that has received limited attention.…”
Section: Uncertainty and Religious Reactivitymentioning
confidence: 99%
“…For example, compared to low scorers, high scores have stronger links between their moods and their thoughts (e.g., Petty, Schumann, Richman, & Strathman, 1993), their thoughts and their attitudes (see Cacioppo et al, 1996), and their attitudes and their behaviors (e.g., Cacioppo, Petty, Kao, & Rodriguez, 1986). They report less uncertainty about the nature of cause and effect relationships in the social world (e.g., Weary & Edwards, 1994) and possess more complex schemata for explaining human behavior (Fletcher, Danilovics, Fernandez, Peterson, & Reeder, 1986). They are also more prone to the effects of subtle priming cues on behavioral and attitudinal responses (e.g., Petty et al, 2008).…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Participants also completed the Causal Uncertainty Scale (CUS). The CUS measures chronic individual differences in causal uncertainty beliefs (Weary & Edwards, 1994). This scale consists of 14 items that express uncertainty about the causes of positive and negative events that happen to the self and others (e.g., "I do not understand what causes most of the good things that happen to me," "When I see something bad happen to others, I often do not know why it happened").…”
Section: Pilot Study 1: Stereotype Knowledgementioning
confidence: 99%
“…Thirty introductory psychology students received packets containing 36 behavior statements followed by the CUS (Weary & Edwards, 1994). For each of the 36 statements, participants were asked to rate on an 11-point scale how useful each piece of information would be in predicting a person's GPA (-5 = very diagnostic of a low GPA, 0 = not diagnostic at all, 5 = very diagnostic of a high GPA).…”
Section: Pilot Study 2: Target Behaviorsmentioning
confidence: 99%